Iron Potentiates Microglial Interleukin-1β Secretion Induced by Amyloid-β - Nnah, Israel C. (J Neurochem, 2020)
Alzheimer’s disease (AD) is characterized by the accumulation of amyloid-beta (Aβ) senile plaques in patients’ brain tissues. Elevated levels of the pro-inflammatory cytokine interleukin-1beta (IL-1β) have been identified in cerebrospinal fluid of living AD patients and in animal models of AD. Increased expression of IL-1β and the accumulation of iron have been identified in microglial cells that cluster around amyloid plaques in AD mouse models and post-mortem brain tissues of AD patients. The goals of this study were to determine the effects of Aβ on the secretion of IL-1β by microglial cells and whether iron status influences this pro-inflammatory signaling cue. To accomplish this goal, immortalized microglial (IMG) cells were incubated with Aβ with or without the addition of iron. qRT-PCR and Western blot analyses showed that Aβ induces the expression and biosynthesis of IL-1β by IMG cells. These microglial cells secrete the mature form of IL-1β in a caspase-1 dependent manner as determined by ELISA. Incubation of IMG cells with iron provoked a greater pro-inflammatory response as measured by these assays. Inhibition of the iron transporter DMT1 protected IMG cells against Aβ-induced inflammation. Potentiation of Aβ-elicited IL-1β induction by FAC was also antagonized by ROS inhibitors, supporting the notion that DMT1-mediated iron loading and a subsequent increase in cellular ROS contribute to the inflammatory effects of Aβ in microglia. Immunoblots and immunofluorescence microscopy data indicated that the presence of iron enhances Aβ activation of NF-κB signaling to promote synthesis of IL-1β. These results support the hypothesis that Aβ stimulates IL-1β expression by activating NF-κB signaling in microglia cells. Most importantly, iron appears to exacerbate the pro-inflammatory effects of Aβ to increase IL-1β levels, most likely through ROS generation. Because IL-1β promotes neuronal degeneration, these results suggest that iron status can profoundly influence the pathogenesis of AD by altering production of this cytokine.